2016
DOI: 10.17511/ijmrr.2016.i03.15
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO blood groups and Rh(D) factor in and around Anatapuramu, Andhra Pradesh

Abstract: Background: India is a vast country with lot of diversity in race, religion and creed. The same diversity has been observed in geographical distribution of blood groups in population within country. ABO and Rh blood groups are most important blood groups in human beings. Objectives: A retrospective study was conducted at Government Medical College/ Government General Hospital Blood Bank Anantapuramu over a period of one year from January 2014 to December 2014 to determine and compare the distribution of ABO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Table 5 shows the variation in ABO blood group and Rhesus factor in Indian and International studies. [ 15 16 17 18 19 20 21 22 23 24 25 26 ] The present study exhibits that A, AB, and Rh negative blood groups are having the highest prevalence of 30.39%, 11.70%, and 6.49% respectively which is comparatively higher than previous similar studies. Another blood group in the present study B is having last second lowest prevalence (31.39%) when compared among Indian studies but international studies were found second highest prevalence percentage.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…Table 5 shows the variation in ABO blood group and Rhesus factor in Indian and International studies. [ 15 16 17 18 19 20 21 22 23 24 25 26 ] The present study exhibits that A, AB, and Rh negative blood groups are having the highest prevalence of 30.39%, 11.70%, and 6.49% respectively which is comparatively higher than previous similar studies. Another blood group in the present study B is having last second lowest prevalence (31.39%) when compared among Indian studies but international studies were found second highest prevalence percentage.…”
Section: Resultsmentioning
confidence: 44%
“…Distribution pattern of blood groups of the present study was compared with the recent studies done across India at Andhra Pradesh,[ 15 ] Jharkhand,[ 16 ] Delhi and Uttarakhand,[ 17 ] Madhya Pradesh,[ 18 ] Karnataka,[ 19 ] and Assam. [ 20 ] The present study revealed that the most common blood group was “B” and the least common was “AB” which is similar to result found in Jharkhand, Delhi, Uttarakhand, and Madhya Pradesh but differs from the other studies.…”
Section: Discussionmentioning
confidence: 99%